The Effectiveness and Application of the School Meal Policy in Improving the Behavior of the High School Students in a Satuan Pendidikan Kerjasama Private School - Syarif Syahman; Kamaluddin; Bintang Simbolon (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2020)
The Effectiveness and Application of the School Meal Policy in Improving the Behavior of the High School Students in a Satuan Pendidikan Kerjasama Private School. The purpose of this study was to explore the possible relationship between the school meal policy towards the high school student’s behavior academically and non academically in school. Student’s behavior is determined by their daily habits in school. These habits will result in their everyday behavior such as their interest in going to school, their honesty in doing test without cheating, having a healthy relationship with their peers and teacher, and their ability to be punctual in ariving to school or respecting the school timetable as a whole. The researcher recommends that the school administrator should utilize the result of this research to make a better meal policy, with the soul objective of honing the student’s dicipline and improving their behavior in school.